2004
DOI: 10.1071/ea02165
|View full text |Cite
|
Sign up to set email alerts
|

Growth, development and nutritional manipulation of marbling in cattle: a review

Abstract: This review describes the pattern of intramuscular fat accretion in cattle and the potential for its manipulation during both the pasture (or backgrounding) and intensive grain-finishing phases of development. A growth curve for the development of marbling in British and Japanese Black type breeds is discussed with the conclusion that 3 phases of development exist: (i) a period of growth up to ~200 kg hot carcass weight where intramuscular fat does not increase; (ii) a period of linear development as carcass w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
169
1
12

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(187 citation statements)
references
References 31 publications
5
169
1
12
Order By: Relevance
“…Overall, odd-chain FA and BCFA in animal fat are primarily derived from rumen microbes compared with de novo synthesis (Vlaeminck et al, 2006). The decrease in odd-chain FA and BCFA in the current study may, therefore, largely related to a direct inhibition of 18:2n-6 on rumen microbes (Vlaeminck et al, 2006) and the reduction of propionate production from readily fermentable starch in the rumen (Pethick et al, 2004). Propionate and its carboxylation product methylmalonate are primers for the biosynthesis of odd-chain FA and BCFA, respectively (Vlaeminck et al, 2006).…”
Section: Lt Fasmentioning
confidence: 57%
“…Overall, odd-chain FA and BCFA in animal fat are primarily derived from rumen microbes compared with de novo synthesis (Vlaeminck et al, 2006). The decrease in odd-chain FA and BCFA in the current study may, therefore, largely related to a direct inhibition of 18:2n-6 on rumen microbes (Vlaeminck et al, 2006) and the reduction of propionate production from readily fermentable starch in the rumen (Pethick et al, 2004). Propionate and its carboxylation product methylmalonate are primers for the biosynthesis of odd-chain FA and BCFA, respectively (Vlaeminck et al, 2006).…”
Section: Lt Fasmentioning
confidence: 57%
“…The profile of postnatal IMF content over development is schematically characterised in Figure 1a. Hudson, Reverter, Greenwood, Guo, Cafe and Dalrymple This was based on the study by Pethick et al (2004), which documented the relationship between carcass weight and IMF% in crossbred Angus × Hereford, Angus and Japanese Black × Holstein cross cattle. We previously identified two closely related sets of fat metabolism genes whose expression was highly correlated (co-expressed) across development (Hudson et al, 2009b).…”
Section: Resultsmentioning
confidence: 99%
“…For each prefinishing growth pathway and market destination, after adjusting for differences in carcass weight between finishing diet, P8 fat, rib fat and IMF% were higher for the feedlot-finished animals. Pethick et al (2004) in reviewing results of the Beef Cooperative Research Centre studies concluded that at the same carcass weight IMF content in pasture-finished animals was reduced by 40% for every 10-kg increase in carcass weight compared with feedlot-finished animals.…”
Section: Discussionmentioning
confidence: 99%